2017
DOI: 10.3390/mi8020032
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Microbeams under Multi-Frequency Excitations

Abstract: This paper presents an investigation of the dynamics of microbeams under multiple harmonic electrostatic excitation frequencies. First, the response of a cantilever microbeam to two alternating current (AC) source excitation is examined. We show by simulations the response of the microbeam at primary resonance (near the fundamental natural frequency) and at secondary resonances (near half, superharmonic, and twice, subharmonic, the fundamental natural frequency). A multimode Galerkin method combined with the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Ebrahim et al [ 50 ] found the maximum amplitude of a clamped-clamped micro-beam of length. The applied voltage is , in which is the oscillation frequency.…”
Section: Simulations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebrahim et al [ 50 ] found the maximum amplitude of a clamped-clamped micro-beam of length. The applied voltage is , in which is the oscillation frequency.…”
Section: Simulations and Discussionmentioning
confidence: 99%
“… Comparison of the results of numerical simulations in this paper with the experimental results [ 50 ]. …”
Section: Figurementioning
confidence: 99%
“…However, the difficulty lies in matching vibration frequencies to the harvester's resonance frequency, and the sensing range is limited in low bandwidth. As a potential solution, researchers have explored the use of nonlinear mechanical resonators to expand the power bandwidth and sensing range [22,23]. More specifically, for wireless ME antennas [24,25], enhancing data transmission speed involves utilizing a nonlinear signal component to effectively separate information bandwidth and radiation from the antenna's limited bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the multi-harmonic excitation in MEMS mixer-filters (Ramini et al, 2016) gives a positive effect in down-conversion and filtering frequencies from radio frequencies to intermediate frequency signals. Vibration of clamped-clamped microbeams in MEMS with periodic excitations are theoretically (Jaber et al, 2016a,b) and experimentally (Ibrahim et al, 2017) investigated. It is shown that there is a benefit of multi-frequency excitations in conversion of the signal in a wide frequency band.…”
Section: Introductionmentioning
confidence: 99%